2013
DOI: 10.1016/j.drudis.2012.07.013
|View full text |Cite
|
Sign up to set email alerts
|

The development and application of small molecule modulators of SF3b as therapeutic agents for cancer

Abstract: The identification of potent spliceosome modulators that demonstrate antitumor activity indicates that this complex may be a target for drug development. Several natural products have been demonstrated to bind to the SF3b1 subunit of this macromolecule and these agents modulate alternative RNA splicing. In this article we describe their biological properties, discuss the validity of the spliceosome as a therapeutic target, and propose that alteration of alternative splicing represents a viable approach for ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(116 citation statements)
references
References 61 publications
(90 reference statements)
1
112
0
1
Order By: Relevance
“…Yet it remains unclear what functional role SF3B1 mutations may play during oncogenesis and whether deregulated SF3B1 activity is required for cancer maintenance. SF3B1 small-molecule inhibitors are currently under development and have entered clinical trials (32). The fact that SF3B1 is part of the spliceosome, however, raises the concern that pan-SF3B1 inhibitors may exhibit significant toxicities in normal tissues and thus present a very narrow therapeutic window.…”
Section: Resultsmentioning
confidence: 99%
“…Yet it remains unclear what functional role SF3B1 mutations may play during oncogenesis and whether deregulated SF3B1 activity is required for cancer maintenance. SF3B1 small-molecule inhibitors are currently under development and have entered clinical trials (32). The fact that SF3B1 is part of the spliceosome, however, raises the concern that pan-SF3B1 inhibitors may exhibit significant toxicities in normal tissues and thus present a very narrow therapeutic window.…”
Section: Resultsmentioning
confidence: 99%
“…SF3b155 is the target of several lead compounds such as spliceostatin A that confer cytotoxicity and anti-tumor effects (for review, see Ref. 48). Furthermore, mutations in the SF3b1 gene encoding SF3b155 occur in Ïł75% of myelodysplastic syndromes with ring sideroblasts (49 -51) as well as chronic lymphocytic leukemia (for review, see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…13 Pladienolide-resistant clones from WiDr and DLD1 colorectal-cancer cell lines shared an identical mutation at Arg 1074 (R1074H) in the SF3B1 gene suggesting that this mutation is critical for its anti-cancer activity via spliceosome modulation. 14,15 Additional work has also identified other small molecules with splicing modulator activity including spliceostatin A, herboxidiene, isoginkgetin, and E7107, a compound that has been tested in phase I clinical studies in which it has shown clinical activity, albeit with unexpected visual toxicities. 16 Additional data will be required to define the role of this and other related compounds as potential anti-cancer agents.…”
Section: Introductionmentioning
confidence: 99%